If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) = 4x + 3 + 20 + 3x Reorder the terms: 4(-3 + 2x) = 4x + 3 + 20 + 3x (-3 * 4 + 2x * 4) = 4x + 3 + 20 + 3x (-12 + 8x) = 4x + 3 + 20 + 3x Reorder the terms: -12 + 8x = 3 + 20 + 4x + 3x Combine like terms: 3 + 20 = 23 -12 + 8x = 23 + 4x + 3x Combine like terms: 4x + 3x = 7x -12 + 8x = 23 + 7x Solving -12 + 8x = 23 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -12 + 8x + -7x = 23 + 7x + -7x Combine like terms: 8x + -7x = 1x -12 + 1x = 23 + 7x + -7x Combine like terms: 7x + -7x = 0 -12 + 1x = 23 + 0 -12 + 1x = 23 Add '12' to each side of the equation. -12 + 12 + 1x = 23 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = 23 + 12 1x = 23 + 12 Combine like terms: 23 + 12 = 35 1x = 35 Divide each side by '1'. x = 35 Simplifying x = 35
| -7x-4=-60 | | 23+17x+1=22x+4 | | x+70=36 | | 18x^3-9x^2-2x= | | 22x+4-17x+1=32 | | 3v^2+5x-8x=0 | | 17x+1+23=22x-4 | | 22x-4-(7x+1)=23 | | -16=-4x+7x-7 | | x+10y=0 | | -40=-7x+3x+8 | | -b^2+6b+7=0 | | 5x+3=3+9x | | 22x+4=23+7x+1 | | X=(-20/(e^(.1x))) | | 7x+1+23=22x+4 | | x(-14)=112 | | (7x+1)+23=22x+4 | | 7y+8-5+6y=9 | | 3x-12=-6+x | | (y+14)+y=32 | | 4s+2=16 | | 2(k+16)=72 | | (7+8)-(5+6y)=9 | | -4x+83=-80 | | 11=5+3y | | 5x+4=7x+4 | | 80=y | | 11=19-2b | | (2x-80)=x | | -2x-28=67-7x | | (5a-3)(5a-3)= |